PERLINDUNGAN HUKUM BAGI PENGGUNA JASA EKSPEDISI ATAS KEHILANGAN BARANG KIRIMAN: STUDI KASUS PADA PT. JNE - Maziz Zidananda Maulana; Miko Aditiya Suharto (Universitas Labuhanbatu, 2026)
The loss of shipped goods in PT JNE’s delivery services causes financial harm to consumers and raises legal issues regarding the liability of service providers. This study aims to analyze the legal protection available to consumers against lost shipments and to examine the legal remedies that may be pursued. The research employs an empirical juridical method with a socio-legal approach, using primary data obtained through interviews with service users and related parties, as well as secondary data from statutory regulations and legal literature. The findings indicate that existing legal protection has not been effectively implemented, as reflected in cases where compensation is not optimally fulfilled. Several respondents reported that the claims process is often complex and lacks transparency, resulting in legal uncertainty for consumers. This condition demonstrates a gap between normative provisions under consumer protection law and their practical enforcement, and suggests potential breach of contract (wanprestasi) by the service provider. Dispute resolution may be pursued through non-litigation mechanisms, such as the Consumer Dispute Settlement Agency (BPSK), or through litigation in court. Therefore, strengthening supervision and law enforcement is essential to ensure consumer protection and enhance the accountability of delivery service providers. Keywords: legal protection; delivery services; PT JNE; compensation; breach of contract